Improving Knowledge and Behavior through Cataract Education in the Pre-Prosperous Community of Tangerang - Mardjuki, Abhimanggala; Larasandi, Agraprana; Silaen, Desi Hartati; Ramadani, Regita Azahra (Jurnal Abmas Negeri (JAGRI), 2025)
Cataracts are one of the main causes of blindness in Indonesia, especially in lower-middle class communities who have limited access to eye health information. Through an education program in the pre-prosperous communities of Tangerang, an intervention was carried out to improve participants' knowledge and behavior regarding cataracts. This program involved collaboration between eye specialists (ophthalmologists), as the main resource persons, and optometris health workers who actively participate. The methods used included providing interactive education by ophthalmologists regarding the causes, symptoms, prevention, and treatment of cataracts, which were complemented by discussion sessions and knowledge evaluation through pre-test and post-test questionnaires. A total of 80 participants filled out a questionnaire containing 10 closed questions before and after education. The results of the analysis showed an increase in the average score of 30,3%. All participants showed an increase in understanding after receiving education, marked by no scores below 67 on the post-test. This activity shows that an educational approach that was adjusted to the community's literacy level is effective in increasing awareness of eye health, especially in preventing blindness due to cataracts.